STRATEGI KOMUNIKASI PARIWISATA KOTA BENGKULU: Studi Unique Selling Proposition Program Visit 2020 Wonderful Bengkulu - Adhrianti, Lisa; Gushevinalti, Gushevinalti; Ningrum, Dyaloka Puspita (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
This study aims to determine the communication strategy of the Unique Selling Proposition (USP) of Bengkulu city tourism for the Visit 2020 Wonderful Bengkulu program based on promotional mix theory which includes advertising, sales promotion, personal selling and public relations. Using a qualitative-interpretive approach, we collected data in the field through in-depth interviews with 9 informants, participant observation, and other document records. The results show that in promoting, ads have not highlighted the uniqueness of tourism potential and media placement of ads that are not distributed in all airlines. On the other hand, Bengkulu City tourism is also relatively promoted only privately and accidently, for example due to official visits by officials. Regarding the public relations strategy, we found inconsistencies between reality in tourism objects and the proclaimed regional government program. Based on these findings, we suggest a more strategic effort to maximize preparations to welcome the Visit 2020 Wonderful Bengkulu. To cite this article (7th APA style):Ningrum, D. P., Adhrianti, L. & Gushevinalti (2018). Strategi Komunikasi Pariwisata Kota Bengkulu: Studi Unique Proposition Program Visit 2020 Wonderful Bengkulu [The Tourism Communication Strategy of Bengkulu City].  Journal Communication Spectrum, 8(1), 45-55. http://dx.doi.org/10.36782/jcs.v8i1.1811